Pengaruh perbedaan salinitas terhadap pertumbuhan kepiting bakau, Scylla serrata - Sitaba, Rifan D.; Salindeho, Indra R.N.; Kusen, Diane J. (e-Journal BUDIDAYA PERAIRAN, 2017)
The aims of the research were to find out firstly, the growth rate of the mud crab Scylla Serrata) reared under different salinity levels and secondly, the range of the salinity where the mud crab optimally grows.   The experiment was conducted at the Laboratory of Aquaculture Technology, FPIK, UNSRAT, from April to May 2017.  The experiment was set up according to the Randomized Block Design, with 3 treatments, which were 3 different salinity levels, 10 ppt, 20 ppt and 30 ppt.  The tested level of salinity was determined based on the preliminary experiment.  Each treatment was triplicated, and each replicate represents the group of the initial weight of the tested crab, which was 80-89 grams (group-1), 70-79 grams (group-2), and 60-69 grams (group-3).  The tested mud crabs were collected from the estuarine waters of Inobonto river, which has salinity level of 12 ppt.  The tested crabs were weighed at the beginning and at the end of the experiment, and at the interval of 7 days during the experiment period.  The weight of the tested crabs data were converted into Absolute Growth Rate (AGR) and Daily Growth Rate (DGR), which in turn were statistically analyzed using Anova for Randomized Block Design, and then Least Significant Difference Test.  The results of the Least Significant Difference Test show that the absolute and daily growth rate of the tested crabs in the salinity of 10 ppt are not significantly different with those in the salinity of 20 ppt.  While the lowest absolute and daily growth rate of the tested crabs were in the salinity of 30 ppt and are significantly different with those in the salinity of 10 and 20 ppt.  Hence, in order to get a maximal production, the mud crab, Scylla serrata, should be cultured in the waters with a range of salinity between 10 and 20 ppt.Keywords: Mud crab, salinity, growth